2019
DOI: 10.1097/txd.0000000000000935
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Liver Transplantation in Patients on Renal Replacement Therapy: Considerations for Simultaneous Liver Kidney Transplantation Versus Safety Net

Abstract: What problem will this proposal solve? Current OPTN policy prioritizes candidates seeking a simultaneous liver kidney (SLK) transplant before pediatric and adult transplant candidates who are listed only for a kidney ("kidney alone candidates") when the liver candidate and the deceased donor are in the same Donation Service Area (DSA) 1. Unlike kidney alone allocation, in SLK allocation, the kidney is not allocated based on medical criteria assessing the kidney function of the candidate. Instead, geographic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Combined liver-kidney transplantation should be considered in patients with severe renal impairment or on renal replacement therapy [ 30 , 31 ].…”
Section: Strategies For Immunosuppression In Liver Transplant Recipiementioning
confidence: 99%
See 1 more Smart Citation
“…Combined liver-kidney transplantation should be considered in patients with severe renal impairment or on renal replacement therapy [ 30 , 31 ].…”
Section: Strategies For Immunosuppression In Liver Transplant Recipiementioning
confidence: 99%
“…Patients with ADPKD and renal impairment and/or in renal replacement therapy are considered for simultaneous or delayed combined liver-kidney transplantation [ 43 , 44 ]. In this case, the immunosuppressive therapy is directed towards the critical patient path or towards the standard case path depending on the clinical conditions and after a careful multidisciplinary evaluation [ 30 , 31 ].…”
Section: Strategies For Immunosuppression In Liver Transplant Recipiementioning
confidence: 99%
“…Recent studies have sought to define the specific ESLD population who best benefit from dual organ transplantation. These showed that SLK improved graft survival in patients with prolonged dialysis-dependent renal failure [6,10] but did not in nondialysisdependent patients [6,11,12]. The ongoing concern is that unregulated renal allograft allocation for SLK reduces organ availability for renal failure patients requiring isolated kidney transplant.…”
Section: Discussionmentioning
confidence: 99%
“…12 A more recent analysis corroborated this and also noted that of patients listed for SLK who underwent LTA prior to 2017, only 7.4% underwent KALT within the first 3 years post LTA. 72 Finally, although previous data had reported superior patient and graft survival in SLK compared with KALT, newer data have shown equivalent outcomes with early KALT. [73][74][75] Thus, an expeditious pathway to KALT is necessary to allow LTA over SLK but to also avoid prolonged KALT wait times and mortality.…”
Section: Kidney After Liver Transplantation: Evolution Of the Safety Net Policy Historical Perspectivesmentioning
confidence: 95%